Forensic Analysis Of A Check Forgery Case: Issues And Implications For Strengthening Internal Control Systems (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze check forgery as a form of document fraud and to evaluate the role of forensic accounting in detecting and preventing such practices through the strengthening of internal control systems. A Literature Systematic Review (LSR) approach is employed, drawing from literature published between 2017 and 2025 and supported by a real-life case study from a financial institution that still operates with manual systems. The findings reveal that fraud was committed through unauthorized check issuance, forged signatures, and cash withdrawals carried out by external actors in collusion with internal personnel. Forensic analysis identified systemic weaknesses, including the absence of segregation of duties, multi-level verification, risk-based auditing, and ineffective implementation of standard operating procedures (SOPs). This study also emphasizes the importance of integrating religiosity as a moral foundation for fraud prevention, aligning with Islamic values that uphold honesty and trustworthiness in all financial dealings. The main contribution of this research lies in providing both conceptual and practical foundations for financial institutions, particularly cooperatives and non-bank entities to build early detection systems and fraud prevention mechanisms that are adaptive to both digital and conventional threats.